2020
DOI: 10.21037/atm-20-1802
|View full text |Cite
|
Sign up to set email alerts
|

Incidence trends and survival outcomes of penile squamous cell carcinoma: evidence from the Surveillance, Epidemiology and End Results population-based data

Abstract: Background: To provide the latest incidence trends and explore survival outcomes of penile squamous cell carcinoma (PSCC) patients with or without a previous primary malignancy.Methods: Patients diagnosed with PSCC between 1975 and 2016 in the Surveillance, Epidemiology, and End Results (SEER) database were retrospectively included. Then, we calculated the age-adjusted incidence rates (IRs) and annual percentage changes (APCs). Multivariate Cox analysis and Kaplan-Meier (KM) survival curves were conducted to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…There were relatively few studies focusing on the trend of penile cancer mortality. A retrospective study, whose data were from the Netherlands during 1989-2006, suggested a slight decrease in mortality (11,29). Similarly, a decrease in mortality was also observed in England for 1979-2009 (30).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There were relatively few studies focusing on the trend of penile cancer mortality. A retrospective study, whose data were from the Netherlands during 1989-2006, suggested a slight decrease in mortality (11,29). Similarly, a decrease in mortality was also observed in England for 1979-2009 (30).…”
Section: Discussionmentioning
confidence: 94%
“…Another possible explanation for this result was that the main population of penile cancer patients was aging. For example, previous studies showed that the most common age of penile cancer patients was between 50 and 70 years (29,39). However, patients aged 75+ years were the main population age group in our study.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 American data assessed using the Survival, Epidemiology and End Results (SEER) program has demonstrated similar or lesser values for the occurrence of penile cancer with suggestions of multifactorial increases in incidence over time. 15,16 Canadian Cancer Statistics data from 2018 indicated an overall incidence rate of approximately 1.05/100,000 when calculated from the Statistics Canada male population at this time. 13 These reports are consistent with current epidemiological interpretations of lower incidence amongst developed nations.…”
Section: Discussionmentioning
confidence: 94%
“…Tumour grade has been shown to be an independent prognostic indictor for penile squamous cell carcinoma, with a higher grade tumour associated with a poorer prognosis. 13 The impact of p16 status on survival outcomes Current evidence suggests that HPV infection in penile cancer carries a better 5-year recurrence-free survival and overall survival than patients who are HPV negative. 12 14 15 HPV infection is also associated with improved loco-regional control of penile squamous cell carcinoma.…”
Section: Hpv Prevalence In An Irish Penile Cancer Cohortmentioning
confidence: 99%